Fall injuries in Baghdad from 2003 to 2014: Results of a randomised household cluster survey. Issue 1 (January 2016) - Stewart, Barclay T.; Lafta, Riyadh; Al Shatari, Sahar A Esa; Cherewick, Megan; Flaxman, Abraham; Hagopian, Amy; Burnham, Gilbert; Kushner, Adam L.
Abstract: Introduction: Falls incur nearly 35 million disability-adjusted life-years annually; 75% of which occur in low- and middle-income countries. The epidemiology of civilian injuries during conflict is relatively unknown, yet important for planning prevention initiatives, health policy and humanitarian assistance. This study aimed to determine the death and disability and household consequences of fall injuries in post-invasion Baghdad. Methods: A two-stage, cluster randomised, community-based household survey was performed in May of 2014 to determine the civilian burden of injury from 2003 to 2014 in Baghdad. In addition to questions about household member death, households were interviewed regarding injury specifics, healthcare required, disability, relatedness to conflict and resultant financial hardship. Results: Nine hundred households totaling 5148 individuals were interviewed. There were 138 fall injuries (25% of all injuries reported); fall was the most common mechanism of civilian injury in Baghdad. The rate of serious fall injuries increased from 78 to 466 per 100, 000 persons in 2003 and 2013, respectively. Fall was the most common mechanism among the injured elderly ( i.e. ≥65 years; 15/24 elderly unintentional injuries; 63%). However, 46 fall injuries were children aged <15 years (49% of unintentional injuries) and 77 were respondents aged 15–64 years (36%). Respondents who spent significant time within the home ( i.e. unemployed, retired, homemaker) had three times greater odds of having suffered a fall injury than student referents (aOR 3.34; 95%CI 1.30–8.60). Almost 80% of fall injured were left with life-limiting disability. Affected households often borrowed substantial sums of money (34 households; 30% of affected households) and/or suffered food insecurity after a family member's fall (52; 46%). Conclusion: Falls were the most common cause of civilian injury in Baghdad. In part due to the effect of prolonged insecurity on a fragile health system, many injuries resulted in life-limiting disabilities. In turn, households shouldered much of the burden after fall injury due to loss of income and/or medical expenditure, often resulting in food insecurity. Given ongoing conflict, civilian injury control initiatives, trauma care strengthening efforts and support for households of the injured is urgently needed.